2021
DOI: 10.1016/j.yrtph.2021.105022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxicity of sodium dodecyl sulphate (SDS) in the MucilAir™ human airway model in vitro

Abstract: The aim of the study was to use multiple in vitro assays to assess the effects of a model irritant, sodium dodecyl sulphate (SDS) (≤10 mM (0.29 %, w/v)), on an in vitro model of the airway, MucilAir™. The use of MucilAir™ in recovery studies was also explored.A 24 h exposure increased IL-8 release at an SDS concentration ≥0.63 mM (0.018 %, w/v). Mucin secretion increased and transepithelial electrical resistance (TEER) decreased at SDS concentrations ≥1.25 mM (0.04 %, w/v). Cytotoxicity (lactate dehydrogenase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…We also characterized the scaffold’s ability to clear from detergent residues by SDS content assessment at different stages of washing. It is known that SDS detergent residues are cytotoxic for cells ( Gilpin et al, 2014 ; Welch et al, 2021 ), with endothelial cells being particularly susceptible ( Zvarova et al, 2016 ). As ECs are crucial for vessel repopulation, we analyzed the SDS concentration at the end of the decellularization procedure and after the application of several washing steps with PBS.…”
Section: Resultsmentioning
confidence: 99%
“…We also characterized the scaffold’s ability to clear from detergent residues by SDS content assessment at different stages of washing. It is known that SDS detergent residues are cytotoxic for cells ( Gilpin et al, 2014 ; Welch et al, 2021 ), with endothelial cells being particularly susceptible ( Zvarova et al, 2016 ). As ECs are crucial for vessel repopulation, we analyzed the SDS concentration at the end of the decellularization procedure and after the application of several washing steps with PBS.…”
Section: Resultsmentioning
confidence: 99%
“… 17 On the other hand, the effect of surface-active agent SDS is considered to be due to its toxicity. 44
Figure 2. Comparison of permeability enhancement between L-R5 and other PEs.
…”
Section: Resultsmentioning
confidence: 99%
“… 48 However, the concentration used here is toxic at 2 mM as reported in literature. 44 The increase in permeability is therefore probably due to cell death induced by this surfactant. TEER results for C 10 would suggest that it was also toxic at a concentration of 8.5 mM ( Figure 2D ).…”
Section: Discussionmentioning
confidence: 99%
“…MucilAir™ tissues in this study showed initial TEER values of 548 ± 65 Ω × cm 2 . Similar to the EpiAirway™ tissues, there were prominent variations depending on the batch ranging from 346 ± 14 to 638 ± 81 Ω × cm 2 [ 37 ]. The difference between different batches of EpiAirway™ tissues suggests differences between donors or prolonged delivery conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the values in this study, IL-6 and IL-8 values in EpiAirway™ tissues were reported as 100–350 pg/mL and 14,500 ± 3000 pg/mL, respectively [ 8 ], and 91 ± 40 pg/mL IL-6 and 5300 ± 220 pg/mL IL-8 [ 36 ]. Interbatch levels of IL-6 and IL-8 secretion in MucilAir™ can vary by a factor of two to four (IL-6: 58 ± 26–205 ± 130 pg/mL and IL-8: 4.14 ± 0.61–8.19 ± 3.29 ng/mL) [ 37 ]. MucilAir™ tissues in this study secreted up to 358 pg/mL IL-6, while IL-8 were around 100 times higher.…”
Section: Discussionmentioning
confidence: 99%